Emotional Distress, Alcohol Use, and Bidirectional Partner Violence Among Lesbian Women. (August 2015) - Lewis, Robin J.; Padilla, Miguel A.; Milletich, Robert J.; Kelley, Michelle L.; Winstead, Barbara A.; Lau-Barraco, Cathy; Mason, Tyler B.
This study examined the relationship between emotional distress (defined as depression, brooding, and negative affect), alcohol outcomes, and bidirectional intimate partner violence among lesbian women. Results lend support to the self-medication hypothesis, which predicts that lesbian women who experience more emotional distress are more likely to drink to cope, and in turn report more alcohol use, problem drinking, and alcohol-related problems. These alcohol outcomes were, in turn, associated with bidirectional partner violence (BPV). These results offer preliminary evidence that, similar to findings for heterosexual women, emotional distress, alcohol use, and particularly, alcohol-related problems are risk factors for BPV among lesbian women.